2017
DOI: 10.1123/jcsp.2016-0043
|View full text |Cite
|
Sign up to set email alerts
|

Collegiate Athletes’ Expectations and Experiences With Mindful Sport Performance Enhancement

Abstract: Although mindfulness training for athletes is an area of increasing interest, few studies have focused on the qualitative experiences of athletes in such programs. Prior to beginning six sessions of mindful sport performance enhancement (MSPE) training, 45 mixed-sport collegiate athletes reported what they hoped and expected to get from the training, and responded afterward to open-ended questions about their experiences. Participants’ responses were coded for themes with high inter-rater reliability. Athletes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 42 publications
2
7
0
3
Order By: Relevance
“…These changes were observed to be stable across all athletes in the intervention phase. This is consistent with other studies that similarly investigated benefits of mindfulness intervention programs in a sport setting, Hasker (2010), Mistretta et al (2017), Josefsson et al (2019), Zadeh et al (2019).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These changes were observed to be stable across all athletes in the intervention phase. This is consistent with other studies that similarly investigated benefits of mindfulness intervention programs in a sport setting, Hasker (2010), Mistretta et al (2017), Josefsson et al (2019), Zadeh et al (2019).…”
Section: Discussionsupporting
confidence: 91%
“…Overall, all athletes experienced improvements in coach-rated performance either during intervention or post-intervention phases, with acute and chronic improvements observed. Consistent with past studies examining mindfulness-based interventions on sport performance (Hasker, 2010;Mistretta et al, 2017;Josefsson et al, 2019;Zadeh et al, 2019), performance in this study was also observed to improve during and after the intervention phase at different rates across individual athletes. Surprisingly, Athlete 1 experienced a minor acute reduction in coach-rated performance during onset of intervention, and even across the intervention phase itself, but rebounded post-intervention to levels above baseline and intervention.…”
Section: Discussionsupporting
confidence: 90%
“…Anxiety as a mental health problem has been studied in the sports field by several researchers. Research has specifically focused on high-level sport performance, given that these athletes are exposed to situations of greater stress and anxiety [32,33,34]. There is therefore a need to study these problems within populations that engage in lower-level physical activity in order to teach and help control the different psychological processes experienced throughout athletes’ careers [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Existen dos tipos de ansiedad no clínica, la referente al rasgo individual que predispone a la persona a responder de forma ávida ante agentes de la vida cotidiana que el individuo interpreta como amenazantes, conocida como «ansiedad rasgo», y la «ansiedad estado», caracterizada por manifestaciones de ansiedad que se producen de forma breve en el tiempo al enfrentar diversos agentes estresores reales (Garcés de los Fayos & Díaz, 2013). La ansiedad ha sido estudiada en el ámbito deportivo por multitud de investigadores, aunque se han centrado en el contexto del alto rendimiento, debido a que es el nivel en el que los deportistas sufren mayores situaciones estresantes que pueden elevar sobremanera los niveles de ansiedad (Carretero, Moreno-Murcia, González, Ponce & Cervelló, 2012;González, Valdivia-Moral, Cachón, Zurita & Romero-Ramos, 2017;Mistretta, Glass, Spears, Perskaudas, Kaufman & Hoyer, 2017;Núñez & García, 2017;Zagalaz, Castro, Valdivia & Cachón, 2017).…”
Section: Introductionunclassified